ՀԱՅԿ ՄԵԼԻՔՅԱՆԻ նոր ձայներիզը - Արծրնու Սարյան Արաքսի (Musical Armenia, 2010)
Article of a Honored Character of RA, Professor of YSC, Araxi Artsrun Saryan covers performing, composing and concert activities of pianist Hayk Melikyan. Reviewing the new CD of pianist, in which sounds works of Arno Babajanyan (“6 pictures”), Arutyun Dellalyan (Sonata “Dedication to Komitas”), Aram Khachaturian (“Poem”), Tigran Mansourian (“Three Pieces”), Lazar Saryan (“Three Postludes”), Hayk Melikyan (processing “Avun- Avun” and the lullaby “Ruri”). The author cites reviews of leading experts on performance culture of the musician. Art of pianist has long gone beyond the fatherland and is appreciated in Europe.